Executive Education after the Pandemic A Vision for the Future - Íñiguez, Santiago; Lorange, Peter (Palgrave Macmillan Cham, 2022)
Business education and executive development has been one of the most fascinating industries in the world and the fastest growing segment of higher education over the past decades. Today, it is experiencing change on a scale unprecedented since the foundation of the first business schools in the early 20th Century, both due to changes in the corporate environment and also due to the impact of the COVID-19 pandemic across all industries. In this context how do you create world-class educational and training institutions that can cope with those challenges, and be rigorous, vocationally relevant and suited to the corporate growing needs in this new fluid world? And how do you combine the very best of traditional academic values with new learning technologies to create an educational model that is fit to compete in the global economy, threatened today by populism, nationalism and economic turmoil? Yet, as daunting as it is, some institutions have already made significant progress in the journey. In this book Santiago Iñiguez de Onzoño, President of IE University, and Peter Lorange, former President of IMD, bring together contributions from leading figures from some of the world’s major universities. They share their experiences in addressing some of the challenges that the industry faces today, such as diversity and inclusion, employability, the role of AI and the advent of innovative new platforms. Packed with case studies of successful initiatives in business education and executive training, this is a truly visionary book. Authors anticipate future trends and share their in-depth knowledge of what it takes to build world-class educational providers – and their vision of higher education in the future.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 3 - Salud y bienestar